Engaged Scholarship and Its Discontents - Tebeje Molla (Social Inclusion)
Engaged scholarship plays a crucial role in shaping collective narratives and fostering inclusive societies. This article explores the concept of engaged scholarship, highlighting both its transformative potential and the discontents that accompany it. Informed by existing literature and personal reflections, the discussion is divided into three key sections. The first section provides a concise overview of engaged scholarship and outlines the conditions that enable its practice. The second section delves into the main discontents of engaged scholarship: narrow definitions of academic work, polarised views on knowledge and truth, restrictive professional guidelines, the potential for backlash, and the risk of burnout. These pitfalls create an environment where scholars may hesitate to engage fully, despite the pressing need for their contributions to public discourse. In the third and final section, the article emphasises the moral imperative of using research for social change and advocates for the creation of supportive ecosystems to help scholars navigate the challenges of public engagement.